UPAYA HUKUM PRAPERADILAN PENETAPAN TERSANGKA TINDAK PIDANA KORUPSI - Fito Hartley Dharmawan; Mugiati (Fakultas Hukum Universitas Borobudur, 2022)
In the life of society, nation and state, it is possible that members of the community behave deviantly, namely by committing unlawful acts or criminal acts of Law Number 31 of 1999 concerning Eradication of Criminal Acts of Corruption as amended by Law Number 20 of 2001 concerning Amendment to Law Number 31 of 1999 concerning the Eradication of Corruption Crimes. Against perpetrators suspected of committing a criminal act of corruption, law enforcement actions must be taken to prove guilty or not based on formal legal provisions, namely Law Number 8 of 1981 concerning the Criminal Procedure Code (KUHAP). One of the legal efforts to ratify or not determine the suspect is the pretrial legal effort. The problem raised in this study is how the legal action of the KPK investigators based on the Criminal Procedure Code in determining the suspect in the criminal act of corruption and how the pretrial legal action for the determination of the suspect in the criminal act of corruption by the KPK investigator. The method used in this research is normative juridical. The competence of the KPK's authority according to Law Number 30 of 2002 concerning the Corruption Eradication Commission is substantively responsible for operations in terms of carrying out legal actions for investigating and prosecuting perpetrators of criminal acts of corruption.